Clinical impact of admission hypothermia in very low birth weight infants: results from Korean Neonatal Network - Na Hyun Lee; Soo Kyung Nam; Juyoung Lee; Yong Hoon Jun (Korean Pediatric Society, 2019)
Background Preterm infants have difficulty maintaining body temperature after birth. However, clinical guidelines advocate that neonatal body temperature should be maintained at 36.5°C-37.5°C. Purpose We aimed to investigate the incidence of admission hypothermia in very low birth weight (VLBW) infants and to determine the association of admission temperature with in-hospital mortality and morbidities. Methods A cohort study using prospectively collected data involving 70 neonatal intensive care units (NICUs) that participate in the Korean Neonatal Network. From registered infants born between January 2013 and December 2015, 5,343 VLBW infants born at less than 33 weeks of gestation were reviewed. Results The mean admission temperature was 36.1°C±0.6°C, with a range of 31.9°C to 38.4°C. Approximately 74.1% of infants had an admission hypothermia of <36.5°C. Lower birth weight, intubation in the delivery room and Apgar score <7 at 5 minutes were significantly related to admission hypothermia. The mortality was the lowest at 36.5°C-37.5°C and adjusted odd ratios for all deaths increased to 1.38 (95% confidence interval [CI], 1.04-1.83), 1.44 (95% CI, 1.05-1.97) and 1.86 (95% CI, 1.22-2.82) for infants with admission temperatures of 36.0°C-36.4°C, 35.0°C-35.9°C, and <35.0°C, respectively. Admission hypothermia was also associated with high likelihoods of bronchopulmonary dysplasia, pulmonary hypertension, proven sepsis, pulmonary hemorrhage, air-leak, seizure, grade 3 or higher intraventricular hemorrhage and advanced retinopathy of prematurity requiring laser therapy. Conclusion A large portion of preterm infants in Korea had hypothermia at NICU admission, which was associated with high mortality and several important morbidities. More aggressive interventions aimed at reducing hypothermia are required in this high-risk population.